Outcomes of Endoscopic Treatment for Plantar Fasciitis: A Systematic Review. Issue 1 (January 2022) - Mercer, Nathaniel P.; Ward, Leona; Hoberman, Alexander; Cronin, Joseph J.; Hurley, Eoghan T.; Kennedy, John G.
Category: Other Introduction/Purpose: Endoscopic plantar fascia release (EPFR) is an established operative treatment for recalcitrant plantar fasciitis. The purpose of this systematic review is to provide a comprehensive review on the outcomes of endoscopic plantar fascia release in the treatment of plantar fasciitis at mid- and long-term follow-up. Methods: A systematic review was performed using, MEDLINE, EMBASE, and Cochrane library databases in May 2020 based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Studies included were evaluated with regards to the level of evidence (LOE) and quality of evidence (QoE) using the Coleman methodological score. Clinical outcomes and complications were also evaluated. Results: Twenty-five studies including 729 feet were included in this systematic review with a mean follow-up of 25.1 months. 18 papers used the American Orthopaedic Foot & Ankle Society (AOFAS) score. The weighted mean preoperative AOFAS score was 55.6 and the postoperative score was 89.6 out of 100. The total number of patients who had complications was 117 of 729 (16.1%). The most common complication was a recurrence of pain experienced by 6.5% of patients (47 of 117). Conclusion: Endoscopic plantar fascia release provides good clinical and functional outcomes in patients with refractory plantar fasciitis. However, this procedure is associated with a moderately high complication rate.